2014
DOI: 10.1111/nph.12682
|View full text |Cite
|
Sign up to set email alerts
|

Different outcomes for the MYB floral symmetry genes DIVARICATA and RADIALIS during the evolution of derived actinomorphy in Plantago

Abstract: Summary The gene network that specifies flower shape in Antirrhinum majus (bilateral floral symmetry or zygomorphy) includes two MYB‐class genes – RADIALIS (RAD) and DIVARICATA (DIV). RAD is involved in establishing the dorsal identity program and its role is to regulate the domain of activity of DIV (the ventral identity program) by restricting it to ventral regions of the flower. Plantago is in the same family as Antirrhinum but has small, radially symmetrical (actinomorphic) flowers derived from a zygomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Furthermore, three Oryza sativa MYB‐related proteins (OsMYBS1–3) regulate expression of the α‐amylase gene in response to sugar accumulation and hormone signals (Feller et al., ; Lu, ). In addition to these roles, some MYB genes like RAD and DIV control the dorsiventral floral symmetry in Antirrhinum majus (Almeida et al., ; Corley et al., ; Galego and Almeida, ; Reardon et al., ). RAD expression is promoted by CYC2 , a CYCLOIDEA TCP transcription factor (Corley et al., ; Costa et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, three Oryza sativa MYB‐related proteins (OsMYBS1–3) regulate expression of the α‐amylase gene in response to sugar accumulation and hormone signals (Feller et al., ; Lu, ). In addition to these roles, some MYB genes like RAD and DIV control the dorsiventral floral symmetry in Antirrhinum majus (Almeida et al., ; Corley et al., ; Galego and Almeida, ; Reardon et al., ). RAD expression is promoted by CYC2 , a CYCLOIDEA TCP transcription factor (Corley et al., ; Costa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In bilateral Lamialean flowers such as Torenia fournieri (Scrophulariaceae), both TfCYC2 and TfRAD1 are also highly expressed in the floral dorsal region and coordinate petal shape and corolla pigmentation (Su et al., ). Conversely, radial symmetry in Lamialean flowers is likely due to the broader homogeneous expression of both CYC and RAD throughout the floral meristem (Reardon et al., ; Su et al., ; Zhong and Kellogg, , b). In bilateral flowers of Dipsacales, RAD paralogs are differentially expressed in the dorsal and ventral floral organs as well as in leaf tissues (Boyden et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the importance of CYC genes in the evolution of floral zygomorphy has been studied extensively in many species, evidence of RAD and DIV involvement is very limited. Recently, it has been proposed that the reversion to actinomorphic flowers in Plantago lanceolata is due to a loss of RAD from the genome (Reardon et al, 2014). In Bournea leiophylla (Gesneriaceae), loss of dorsal expression of BlCYC and BlRAD during the later stages of flower development led to up-regulation of BlDIV in the entire flower, which in turn generated a final actinomorphic structure (Zhou et al, 2008).…”
mentioning
confidence: 99%
“…Interestingly, the results indicated this syntenic block was retained from a whole genome duplication event taken place during the time span of the zygomorphic flower emergences (about 60 million years ago). Furthermore, downstream CYC/DICH , two genes ( DIV and DRIF ) in RAD / DIV module have homologous copies with similar Ks as CYC / DICH , while DRIF is located at a WGD derived syntenic block 19,20,21 . Those analyses showed that the master regulators of zygomorphic flower were retained from the recent whole genome duplication, revealing the evolutionary base for the zygomorphic flower maintenance in A. majus and perhaps other close relatives.…”
Section: Resultsmentioning
confidence: 99%